PENGARUH KEMAMPUAN KERJA, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PD. BPR BKK KEBUMEN - Hesty Mei Putriana; Jajuk Herawati (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2018)
The purpose of this study was to analyze the effect of work ability on employee performance, the effect of job satisfaction on employee performance, the influence of organizational commitment to employee performance, and the effect of variable ability to work, job satisfaction and organizational commitment on the performance of PD. BPR BKK Kebumen. The sampling technique was accidental sampling. Data collection using a questionnaire, while data analysis techniques using multiple regression analysis by the F-test and T-test and the classical assumption test of normality test, multicollinearity test, and heteroscedasticity. The results showed the multiple linier regression model is Y = 51,096 – 0,263X₁ - 0,305X₂ + 0,293X₃ . That is ability to work, job satisfaction, and organizational commitment contributes greatly to the performance. Value of the determinant coefficient (R²) was 0,158. The result shoe that the coefficient determinant of ability to work, job satisfaction, and organizational commitment have a positive influence on employee performance by 15,8% and the remaining 84,2% is influenced by other factors.